Modeling of Discrete Networked Control Systems in State Space for Electrical Power System with Time Delays: نمذجة نظم التحكم الشبكية المتقطعة في فضاء الحالة لنظام قدرة كهربائية مع وجود التأخيرات الزمنية - Mohamad Morhaf Bachar Alnifawi, Bassem Omran, Jomana Mahmoud Diab (Journal of engineering sciences and information technology, 2021)
Electrical power systems distributed over wide geographical areas are exposed to a set of factors that affect their stability. The most important factors are the time delays between their subsystems. In this paper, a flexible modeling method was concluded consisting of a set of generalized rules and conditions that apply to any network controlled system to ensure its stability with time delays between the elements of the controlled network. In addition, a linear quadratic regulator (LQR) controller was implemented. The aim of the LQR controller is to reduce the negative impact of the time delay on the stability of the electrical power system. The study was applied to a networked electrical power system consisting of three-generation stations distributed in three separate geographical areas. Computer simulations using MATLAB showed a remarkable improvement in the stability of the discrete networked system through the speed of damping the vibrations in the system, and the system ability to be stable at certain limits of the time delay.